Transformasi Ritual Pernikahan Adat Bugis-Makassar di Era Digital: Negosiasi Identitas Budaya antara Tradisi dan Modernitas - Ainun Fatimah; Nurasia Natsir (Universitas Palan, 2026)
Traditional wedding rituals constitute intangible cultural heritage rich in symbolic meaning, serving to strengthen social solidarity and transmit cultural values. The massive penetration of modernization and digitalization has created new pressures for the Bugis-Makassar community in maintaining this heritage. This study analyzes the transformation of Bugis-Makassar traditional wedding rituals in South Sulawesi within the digital era context, focusing on how the community negotiates their cultural identity between the forces of tradition and modernity. Using a critical ethnographic approach with a multiple case study design grounded in Bhabha's concept of the third space, the study involved 42 informants from three groups: young couples (digital generation, aged 22–35), parents/family (middle generation, 40–60), and customary elders (to panrita lopi/bissu, 65+) in Makassar City, Bone Regency, and Wajo Regency. Data were collected through in-depth interviews, participant observation in 12 wedding ceremonies, and social media content analysis. Results reveal three main transformation patterns: (1) digital spectacularization—rituals adapted for social media consumption; (2) reflective selectivity—young couples actively choosing which traditional elements to retain; and (3) procedural hybridization—the integration of customary procedures with contemporary elements. These transformations are colored by intergenerational contestation that generally ends in compromise between demands for customary completeness and the aesthetic preferences of the younger generation. The study concludes that this transformation is not merely a loss of tradition, but a creative form of identity negotiation in which the Bugis-Makassar community actively reconstructs the meaning of siri' (self-esteem/dignity) and pesse (solidarity) within the changed socio-cultural landscape. The findings imply the need for cultural preservation policies that understand change as inherent to living culture, and open avenues for longitudinal studies on the intergenerational transmission of cultural values.